Application of mathematical analysis in the design of permanent magnet motors - Hajdinjak, Melita; Mavrič, Martin; Miljavec, Damijan (Anali PAZU, 2022)
The development of permanent magnets with high energy density and their availability on the market affect the increased use of magnets in synchronous motors. The efficiency of the permanent magnet machine is highly influenced by the magnetic field in the air-gap between the rotor and the stator, which is generated by the rotor with its permanent magnets during rotation. The magnetic field in the air gap and in the permanent magnets of the rotor is obtained as the solution of a system of partial differential equations describing the magnetic properties of the machine. This system is not always fully analytically solvable.
Keywords: permanent magnet motors; magnetic field in the air gap; partial differential equations